Orthographic Features of the Mula Mustafa Bašeskija Chronicle (Prilozi za orijentalnu filologiju, 2017)
The paper deals with the orthographic features of The Chronicle written in the second part of the 18th century by the Bosniak Mula Mustafa Bašeskija in Turkish. Examples of lexical and grammatical morphemes noted down in a graphic picture different from the accepted Ottoman-Turkish orthography of the time are analysed. Departures from the orthography in marking Arabic and Persian lexemes are relatively rare in The Chronicle. In this lexical layer, the mixing of different graphies is noticed in some places that in Turkish have the same phonic value.In marking Turkish lexemes and suffixes, in some places we can trače departures from the orthography of the time. The reasons behind this are various.In some examples, a double way of spelling is noted as a result of the mixing up of the graphemes having the same phonic value. This type of departure is easily noticed and does not affect the determination of the phonetic picture of the analysed linguistic element.In some examples, the graphic differences are the result of mixing traditional orthography and spoken language. Such departures are interesting from the point of linguistic research because they reflect the real status of the language at that time.The spelling of some of the lexemes and suffixes reflect their phonetic picture in the Turkish language as spoken in Bosnia. Such examples are relevant for getting to know the dialect features of that speech.In the spelling of some lexical and grammatical morphemes, we can notice that the vvriter used the graphies being in use in the local Aljamiado literacy. So some of the phonemes were written down in the graphies having originally other phonetic values. Such departures are only of graphic nature and do not reflect real pronunciation.